Retrospective analysis of healthcare workers admitted to emergency department due to side effects of the inactivated COVID-19 vaccine - Yıldırım, Çağdaş; Işık, Nurullah İshak (Acta Medica, 2023)
Objective: This study aimed to evaluate the clinical characteristics and outcomes of healthcare workers who presented to the emergency department with vaccine-related reactions following the first dose of the CoronaVac vaccine. Materials and Methods: A retrospective analysis was conducted in Ankara Bilkent City Hospital’s Emergency Department between 13.01.2021 and 13.02.2021, encompassing healthcare workers aged 18 and above who experienced Vaccine Adverse Effects after CoronaVac vaccination. Data regarding demographics, medical history, symptoms, treatments, and outcomes were extracted from the hospital management system and analyzed using SPSS Version 24. Results: Of the 43 healthcare workers presenting with Vaccine Adverse Effects, 76% were female. Known history of anaphylaxis/urticaria was recorded in 32.6% of the patients, while 11.6% had a prior history of COVID-19. Common presenting symptoms included chest pain (16.3%) and headache (14%). A majority (58.1%) required no treatment, though two patients received adrenaline for anaphylaxis, with one requiring hospitalization. The median time from vaccination to symptom onset was approximately 16 hours. Conclusion: The study demonstrates a higher incidence of Vaccine Adverse Effects among female healthcare workers and those with a history of anaphylaxis/urticaria, although most reactions were mild and did not necessitate treatment. This analysis sheds light on the CoronaVac vaccine’s safety profile among healthcare workers and provides a foundation for addressing vaccine-related concerns in preparation for future mass vaccination endeavors against emerging COVID-19 variants or new pandemics.